Induction Time to Vaginal Delivery: A Comparison of Obstetric Coverage Models - Lao, Amberly; Sommers, Taylor; Kim, Julia; Maldonado, Delphina; Drohan, Lilly; Kantorowska, Agata; Vahanian, Sevan A.; Rekawek, Patricia; Suhag, Anju; Wat, Karyn (American Journal of Perinatology)
Objective: Induction of labor (IOL) and hospitalist coverage is becoming more common. While hospitalist coverage has been associated with improved maternal outcomes and lower cesarean delivery rates, its impact on IOL remains unclear. The objective of this study was to compare the induction time to vaginal delivery across three obstetric coverage models: hospitalists, faculty generalists, and private practice generalists. Study Design: This single-site retrospective cohort study analyzed singleton, term (≥39 weeks), vertex patients undergoing induction of labor at NYU Langone Hospital- Long Island from January 1 to September 30, 2022. Hospitalists at this institution managed high-risk obstetric patients including those under maternal-fetal medicine care, resident clinic, and unregistered patients who presented to labor and delivery, along with serving as labor and delivery safety officer on the labor floor. Faculty and private practice generalists managed their respective groups. Outcomes included induction time to vaginal delivery, mode of delivery, induction methods, and maternal and neonatal complications. Statistical analyses included chi-square, ANOVA, and multivariable linear regression. A p-value <0.05 was statistically significant. Results: Among 403 patients, 92 (22.8%) were managed by hospitalists, 115 (28.5%) by faculty, and 196 (48.6%) by private generalists. Median (IQR) induction-to-delivery times were similar across groups—hospitalists 20.5 (15.3—27.5) h, faculty 23.4 (16.5—31.1) h, and private 19.7 (14.1—25.6) h (p = 0.004). However, when limited to vaginal deliveries, no significant difference was observed in induction-to-vaginal-delivery time (p = 0.17). Private generalists had the shortest induction-to-cesarean time and time to membrane rupture leading to cesarean. There were no differences in intrapartum complications. Hospitalists had more NICU admissions after vaginal delivery, mostly unrelated to labor. Conclusion: Induction-to-vaginal delivery times and complication rates were similar across coverage models, but differences in NICU admissions and cesarean delivery times highlight care variations. Collaboration and evidence based standardized induction protocols may optimize outcomes across coverage models